THE INFLUENCE OF DIGITAL ENTREPRENEURS AND CONSUMER BEHAVIOR ON PRODUCT PURCHASING DESICIONS - Muh Fahrurrozi; Mispandi; Dukha Yunitasari (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
In the digital era, technological advancements have significantly impacted how consumers make purchasing decisions. Study aims to analyze the influence of digital entrepreneurs and consumer behavior on purchasing decisions. This study uses a quantitative approach with a sample of 100 respondents selected randomly. The data analysis technique used is Smart PLS 4.0 to examine the relationships between the variables of digital entrepreneurs, consumer behavior, and purchasing decisions. The results of the study show that digital entrepreneurs do not have a significant effect on purchasing decisions. Meanwhile, consumer behavior has a positive and significant effect on purchasing decisions. The findings of this study are expected to provide insights for business players, especially digital entrepreneurs, to better understand the factors influencing consumer purchasing decisions. In addition, these results can serve as a reference for future research focusing on other aspects that affect purchasing decisions in the context of digital marketing.